Learning technology for education challenges : 6th International Workshop, LTEC 2017, Beijing, China, August 21-24, 2017, Proceedings /: 6th International Workshop, LTEC 2017, Beijing, China, August 21-24, 2017, Proceedings. (2017) - Unknown
No abstract available